ADVANCES AND CHALLENGES IN MINIMALLY INVASIVE SURGERY FOR THE TREATMENT OF HERNIAS - Pedro do Valle Varela, João; Filipe Silva Oliveira, Luís; Edas Corteletti Pereira Lopes, Victor; Gaspar Calzolari, Júlia; Maria Eccard André, Andresa; Teófilo da Silva, Kaicki; Djosci Coêlho de Sá, Henrique; Carlos Mendes Campos, Walter; Marcelo Pacheco Kokis, João; Peçanha Souza, Igor (Health and Society, 2024)
Minimally invasive surgery has revolutionized the treatment of various medical conditions, offering significant benefits in terms of recovery and fewer complications. In the field of hernia surgery, technological advances and innovative techniques have provided a less invasive approach that minimizes pain, reduces recovery time and improves aesthetic results. However, despite notable advances, there are still challenges and limitations that need to be addressed in order to optimize results and expand the use of these techniques. This summary examines the main advances in minimally invasive surgery for the treatment of hernias and discusses the challenges that remain in this field. The aim of this paper is to review recent advances in minimally invasive surgery for the treatment of hernias, highlighting technological innovations, improved techniques and clinical benefits. It also aims to identify the challenges and limitations associated with these techniques, providing a comprehensive overview of the positive and negative aspects of minimally invasive surgery in current clinical practice. This is a bibliographic review, using qualitative and quantitative assumptions, using the PubMed, Scopus and Web of Science databases. The health descriptors “Abdominal Hernia”, “Minimally Invasive Surgery”, “Hernia Repair”, “Hernia Mesh” and “Technological Advances” were used to refine the research. The time frame covers the years 2015 to 2021. Advances in minimally invasive hernia surgery have been driven by the development of advanced technologies such as laparoscopy and robotics. Laparoscopy, which uses small incisions and a camera to guide the surgery, has established itself as the standard technique for treating inguinal and umbilical hernias. This approach offers several advantages over traditional open surgery, including less post-operative pain, a lower risk of infection, reduced hospitalization time and a faster recovery. Laparoscopy allows the surgeon to accurately visualize and repair the hernia, while the small incisions result in smaller scars and a better aesthetic appearance. Recently, robotic surgery has emerged as a significant innovation in the field of minimally invasive surgery. Robotic systems offer a three-dimensional view and greater precision during the operation, allowing for more delicate and complex maneuvers. This technology is particularly useful in cases of complex or recurrent hernias, where precision and control are critical. Studies have shown that robotic surgery can further reduce post-operative pain and recovery time, although the high cost and need for specialized training are challenges associated with this technology. However, the adoption and effectiveness of minimally invasive techniques for hernias face several challenges. One of the main challenges is the learning curve associated with new technologies. Laparoscopy and robotic surgery require advanced technical skills and extensive training, which can limit access to these techniques in some medical centers and regions. Furthermore, although minimally invasive surgery offers significant advantages, patient selection is crucial. Patients with very large hernias, additional complications or medical conditions that increase surgical risk may not benefit as much from these techniques. Another challenge is cost. The advanced technologies and equipment required for minimally invasive surgery are generally more expensive than traditional approaches. These costs can be a barrier to widespread adoption, especially in settings with limited budgets or where access to cutting-edge technologies is restricted. It is concluded that advances in minimally invasive surgery for the treatment of hernias have provided significant benefits, including less post-operative pain, faster recovery and better aesthetic results. Technologies such as laparoscopy and robotic surgery have revolutionized the surgical approach, offering new opportunities for treatment with less impact on the patient. However, challenges such as the learning curve, high cost and the need for careful patient selection need to be addressed in order to optimize practice and expand access to these techniques. As technology continues to evolve and more data becomes available, minimally invasive surgery is expected to become even more effective and affordable, offering continuous improvements in care and outcomes for hernia patients.